Big Nate : blow the roof off! - Peirce, Lincoln (Andrews McMeel Publishing, 2020)
A collection of full-color comic strips following the adventures of Nate and his friends in middle school as they play in their band "Enslave the Mollusk," navigate school with Mrs. Godfrey and Coach John, and learn that Nate's summer crush Trudy is a seventh grader! Includes a pull-out poster.